Generation of Surface Sausage Oscillations of a Current Sheet and Propagating Magnetoacoustic Waves by Impulsive Reconnection - Sripan Mondal; A. K. Srivastava; David I. Pontin; Eric R. Priest (The Astrophysical Journal)
Magnetic reconnection and magnetohydrodynamic waves may well be both playing a role in coronal heating. In this paper, we simulate reconnection in the corona as a response to the convergence of opposite-polarity magnetic sources at the base of the corona. A current sheet forms at a magnetic null and undergoes impulsive bursty reconnection, which drives natural modes of oscillation of the current sheet by a process of symbiosis. These are leaky surface sausage modes, which cause the length of the current sheet to oscillate. Interaction of the oscillations and reconnection outflows with the magnetic Y-points at the ends of the sheet acts as sources for magnetoacoustic waves. Fast-mode waves propagate outward into the coronal environment, while slow-mode waves propagate along the separatrices extending from the ends of the current sheet. The periodicities for sausage oscillations of the current sheet, for the current sheet length, and for the propagating large-scale magnetoacoustic waves are all estimated to be approximately 91 s for the parameters of our experiment.